Preliminary Study on the Effect of Food Bar Supplementation on Food Intake and Body Weight in a Wistar Rat Malnutrition Model - Widyaningsih, Tri Dewanti; Hidayatullah, Apriliawan; Hapsari, Tara Krisda; Kinanti, Agisty Anggunfajar; Febriyantiningtyas, Shani’na; Wulan, Siti Narsito; Nisa, Fithri Choirun (Indonesian Journal of Human Nutrition, 2025)
Stunting remains a critical public health issue in Indonesia, where 2022 prevalence of 21.6% was still categorized as high according to WHO standards (> 20%). One of the direct causes of stunting is inadequate nutrition intake. Food bars formulated from local ingredients such as pumpkin paste, edamame flour, snakehead fish flour, and moringa leaf flour are a promising alternative for supplementary feeding. This present study aimed to evaluate the effects of food bar supplementation on dietary intake and body weight in a Wistar rat model of malnutrition. The study was conducted in two stages using a post-test-only design. In the first stage, malnutrition was induced through the administration of a low-protein diet for 21 days. In the second stage, malnourished rats received a 28-day intervention consisting of K3 (standard diet), K4 (standard diet with 30% food bar), and K5 (standard diet with 50% food bar), while K1 (normal diet) and K2 (continued low-protein diet) served as controls. Rats in the K5 group achieved a final body weight of 116.0 ± 8.4 g, which was significantly higher than that of the K2 group (101.5 ± 13.6 g; p < 0.05), and their food intake also improved. The supplemented groups showed better general condition, including fur growth and activity. These results suggest that food bar supplementation is associated with increased intake and weight gain in malnourished rats; however, further studies involving biochemical markers are needed to assess full nutritional recovery and human applicability.